Pengaruh Inflasi, Financing To Deposit Ratio (FDR) Dan Efisiensi Operasional Terhadap Return On Asset (ROA): Studi Kasus Bank Syariah Listing BEI - Nida Nurhayani Pohan; Kamilah Kamilah; Rahmat Daim Harahap (Journal of Islamic Economics and Finance, 2023)
This study aims to analyze the effect of inflation, financing to deposit ratio (FDR), and operational efficiency on return on assets (ROA) in the financial sector. ROA is an important performance indicator for financial companies, because it reflects the level of profitability of the assets owned. The research method used is regression analysis with annual data from various financial companies during the study period. Inflation is measured using the consumer price index (CPI), FDR describes the ratio between loans provided by banks and deposits received from customers, and operational efficiency is measured by the ratio of operating costs to operating income. The results of this study provide useful insights for the management of financial companies in facing challenges from economic and operational factors. To increase ROA, companies need to consider effective inflation risk management strategies and optimize the FDR ratio, while still focusing on improving their operational efficiency.